Концепция соотношения сознательного и стихийного В.И. Ленина: опыт оценки - Лакиза, А.А. (Культура народов Причерноморья, 2006)
В статье представлен опыт оценки концепции соотношения сознательного и стихийного В.И. Ленина. Его структуру определяет последовательность решения задач, которая обеспечивает установление достижений и недостатков концепции соотношения сознательного и стихийного В.И.Ленина в истолковании этого соотношения. Сначала выделяются компоненты, образующие структуру теории соотношения сознательного и стихийного; затем выясняется, каким образом они раскрываются в концепции В.И. Ленина; после этого указываются критерии, по которым могут оцениваться философские концепции, определенным образом истолковывающие соотношение сознательного и стихийного; в соответствии с установленными критериями дается оценка как концепции соотношения сознательного и стихийного В.И. Ленина в целом, так и ее отдельным компонентам. В заключение делаются выводы о тех отношениях, в которых рассмотренная концепция В.И. Ленина может быть оценена позитивно и негативно. In the article the experience of estimation of conception of the alignment of conscious and elemental of V.I. Lenin is presented. Experience's structure is determined by the sequence of decision of tasks, which provides establishment of the achievements and lacks of the conception of the alignment of conscious and elemental of V.I. Lenin in the interpretation of this alignment. The components which form the structure of the theory of alignment of conscious and elemental are designated at first; then it appears, how they are being revealed in V.I. Lenin's conception; after this the criteria on which philosophical conceptions can be estimated are indicated, definitely interpreting the alignment of conscious and elemental; in accordance with the established criteria the estimation is given both of conception of alignment conscious and elemental of V.I. Lenin as a whole, and of its separate components. Inferences about those relations in which the considered conception of V.I. Lenin can be appraised positively and negatively are drawn in conclusion.